2021
DOI: 10.3390/nano11030815
|View full text |Cite
|
Sign up to set email alerts
|

Nanoemulsions for Enhancement of Curcumin Bioavailability and Their Safety Evaluation: Effect of Emulsifier Type

Abstract: This work aimed at evaluating the effects of different emulsifiers on curcumin-loaded nanoemulsions’ behavior during digestion, its safety and absorption, to develop nanoemulsions that provide safety and improved curcumin functionality. Nanoemulsions (NEs) were produced using two bio-based (lecithin (LEC) and rhamnolipids (RHAM)) and one synthetic (Tween®80 (TWE)) emulsifier at similar concentrations. Different NEs were subjected to in vitro digestion. The cytotoxicity and permeability tests were performed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…The cell viability of caco-2 cells was found to be 87 ± 3.4% at 100 μg/mL of rhamnolipid (Khan et al, 2022). On the contrary, a study by Gonçalves et al (2021) reported cytotoxicity of rhamnolipid-NE on the same cell line owing to a very high concentration (25,000 μg/mL) of rhamnolipid used. The safety of rhamnolipid-NE on plant systems has also been assessed by Mottola et al (2023), wherein Arabidopsis thaliana leaves were exposed to rhamnolipid-NE (200 μg/mL rhamnolipid).…”
Section: Toxicity Of Biosurfactants and Its Nementioning
confidence: 90%
“…The cell viability of caco-2 cells was found to be 87 ± 3.4% at 100 μg/mL of rhamnolipid (Khan et al, 2022). On the contrary, a study by Gonçalves et al (2021) reported cytotoxicity of rhamnolipid-NE on the same cell line owing to a very high concentration (25,000 μg/mL) of rhamnolipid used. The safety of rhamnolipid-NE on plant systems has also been assessed by Mottola et al (2023), wherein Arabidopsis thaliana leaves were exposed to rhamnolipid-NE (200 μg/mL rhamnolipid).…”
Section: Toxicity Of Biosurfactants and Its Nementioning
confidence: 90%
“…Currently, nano-delivery systems are commonly employed to enhance drug dissolution and facilitate the transport of hydrophobic drugs to target tissues (13). Encapsulating curcumin in nanoscale carrier systems such as nanoemulsion signi cantly enhances the e ciency of curcumin, including its bioavailability and solubility (14). The primary classi cations of oil-in-water (O/W) and water-in-oil (W/O) nanoemulsions consist of two immiscible liquids with a surfactant for stabilization.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to mention that the smaller the particle size, the higher the degradation rate of the compound [18]. The efficiency of NE to be absorbed by enterocytes is depend on their diameter (20-200 nm); also, the chain length of the oil incorporated is highly related to the bioaccessibility of the bioactive [19]. The advantage of using a designed emulsifier may represent greater abilities and controlled qualities that can be conferred to the system.…”
Section: Introductionmentioning
confidence: 99%